Oral History Interview with Vesta Buetow, February 2008 - Buetow, Vesta; Ramsey, Allen (My University, 2009)
Vesta Buetow was a physical education teacher and fencing coach. This oral history interview was conducted by Allen Ramsey in support of his MA thesis research on Title IX and women's athletics at the University of Wisconsin--Eau Claire. His thesis, entitled "Continuing to Chip-Away" : How Title IX Changed Athletics at the University of Wisconsin-Eau Claire," is available in the University of Wisconsin--Eau Claire McIntyre Library.
Keywords: Sex discrimination in sports --Wisconsin --Eau Claire --History.; College sports --Wisconsin --Eau Claire --History.; United States. Education Amendments of 1972. Title IX.; Women athletes --Wisconsin --Eau Claire --History.; College sports for women --Wisconsin --Eau Claire --History.; University of Wisconsin--Eau Claire --Sports --History.